ANALISIS KEUNGGULAN KOMPARATIF DAN KOMPETITIF KAIN TENUN SUTERA PRODUKSI KABUPATEN GARUT (Studi Kasus pada Perusahaan PT. Aman Sahuri di Kabupaten Garut Provinsi Jawa Barat) - Dewi Gustiani; Manuntun Parulian Hutagaol (Departemen Agribisnis, FEM-IPB, 2009)
Silk is a industrial product originated from agriculture. This product is important in the national economy. Garut District is one of central area of silk production in Indonesia. Silk produced in Garut is populer among foreign tourists, especially tourists from Netherland, Germany and Japan. The objective is evaluating comparative and competitive advantages of silk products produced in Garut. It is also designed to determine the impact of changes in input and output prices of silk on its comparative and competitive advantage of silk products produced in Garut. This study reveals that silk products of Garut has both comparative and competitive advantage. However, if wage rate and fuel price increase by 15 % and 50 % respectively, the products have no more competitive, but comparative advantage. To improve its competitiveness, agribusiness approach should be integrated into the silk industry.